Econometric analysis of the relationship between public military expenditures and economic growth (in a number of developing countries) - Khaled Haider (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The governments of various countries in general and developing countries in particular, are increasingly concerned with their military aspect, mainly the defense of their achievements so far. That is in addition to protecting internal security, and the pursuit of political stability, which is the most important axis for providing a suitable environment for the exercise of various economic activities. The amounts allocated to that type of spending are deducted from the budgets of those countries (built - as an estimate - on their GDP) on a specific direction by the governments. Those spending amounts are, because of this allocation or deduction, negatively affect other essential fields to human lives such as education and health, and also other fields such as agriculture, industry, infrastructure, etc. The question arises as to the extent of the existence of an opposite relationship (i.e., in the other direction) between military expenditures and the GDP of the countries concerned. Also, seeking to reduce these potential negative effects, so that military public spending would positively affects GDP by moving the economy towards economic growth, which may gradually lead to economic development (For developing countries). This research investigates the existence of this relationship and through the use of a certain number of developing countries and for the years (1990-2017) within the approved model and uses the SPSS application to prove the validity of the research hypothesis.